Using forward end-sweep to reduce transonic cantilevered stator losses to improve compressor performance. Issue 1 (1st January 2018) - Lu, Hanan; Li, Qiushi; Pan, Tianyu
ABSTRACT: The complicated flows in a transonic cantilevered stator would cause serious aerodynamic losses and reducing these losses would contribute much to improving the overall aerodynamic performance of a compressor. The paper conducts an overview study of the potential aerodynamic losses in a transonic cantilevered stator and presents a systematic numerical study for the effects of forward end sweep on reducing aerodynamic losses. A 2-D stator blade is used to throw light upon the physical mechanism of the forward end sweep on reducing the losses. At the casing region, forward end sweep has led to a redistribution of the blade load along the chordwise direction, higher in the front part and lower in the rear part. This result leads to a lower pressure gradient from the 30% chord location to the trailing edge and can be beneficial for the reduction of the corner separation. At the hub region, on one aspect, forward end sweep reduces both the peak Mach number and the size of the high-Ma region of the blade suction surface, thus decreasing the shock loss near the hub. On the other aspect, it also reduces the peak load and the strength of the leakage vortex, therefore alleviating the flow blockages. Simultaneously, the forward end sweep is applied to a commercial and high-performance multistage compressor to further validate its feasibility. When the technique is applied to the transonic first four stator rows, an improvement of adiabatic efficiency is achieved by ∼ 0.85% and the compressor stable operating range is slightly increased. The results suggest that the forward end-swept transonic cantilevered stators have a significant potential for reducing the stator losses. They would provide guidelines to advance the cantilevered stator design and further improve the compressor aerodynamic performance. Abbreviations: h, stagnation enthalpy;, stagnation pressure; p, static pressure; U, blade rotational speed at tip; V, velocity;, non-dimensional wall distance;, total pressure loss coefficient;, flow coefficient ( Vx / U );, stage load coefficient (Δ h / U 2 );, adiabatic efficiency;, total pressure ratio; in, inlet; out, outlet; LE/TE, leading/trailing edge; PS/SS, pressure/suction surface